Effectiveness of Audio-Visual Health Education on Adolescent Sexual and Reproductive Health Awareness in Bengkulu - Waytherlis Apriani; Suhita Tri Oklaini (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Adolescent sexual and reproductive health (SRH) remains a major public health concern, particularly due to limited knowledge, negative attitudes, and risky behaviours among adolescents. Innovative educational approaches such as audio-visual media are needed to improve adolescents’ awareness and understanding of SRH issues. Objective: This study aimed to determine the effectiveness of audio-visual health education in improving adolescents’ sexual and reproductive health knowledge, attitudes, and behaviours. Method: This study employed a quasi-experimental design using a one-group pretest–posttest design without a control group. The study involved 75 tenth-grade students at a senior high school in Bengkulu, Indonesia. Participants received audio-visual-based SRH education over a two-week intervention period. Data were collected using a validated questionnaire assessing knowledge, attitudes, and behaviours related to sexual and reproductive health. Data analysis was performed using descriptive statistics and paired sample t-tests with a significance level of 0.05. Result: The findings showed significant improvements in all measured variables after the intervention. The mean knowledge score increased from 47.72 to 50.64, attitude score increased from 45.48 to 49.41, and behaviour score increased from 45.48 to 54.53. Statistical analysis indicated that the differences between pre-test and post-test scores were significant for knowledge, attitudes, and behaviours (p < 0.001). Conclusion: Audio-visual health education was effective in improving adolescents’ knowledge, attitudes, and behaviours regarding sexual and reproductive health. The findings suggest that multimedia-based educational interventions may serve as an effective strategy for adolescent reproductive health promotion in school settings.